IGF1 Genetic Polymorphism and the Association between Vitamin D Status and BMI Percentiles in Children - Sigal Eilat-Adar; Eias Kassem; Mahmood Sindiani; Sigal Ben-Zaken (MDPI AG, 2023)
Both the IGF1 axis and hypovitaminosis D play a role in childhood obesity, either as a cause or a causality. While some studies suggest an interrelation between vitamin D status, IGF1, and obesity, this mechanism remains obscure. The aim of this study, therefore, was to explore associations between four genetic polymorphisms in the IGF1 axis in hypovitaminosis D-related obesity. The study included 116 pre-pubertal Israeli Arab children (52 girls), mean age 9.4 ± 2.6. Serum 25(OH)D was measured and anthropometric measures were obtained. Genomic DNA was extracted from peripheral EDTA-treated anti-coagulated blood using a standard protocol. Genotypes were determined using the Taqman allelic discrimination assay. The IGF genetic score was computed according to the additive genetic score model. A moderate-to-high negative correlation (r = 0.580, p < 0.05) was seen between the vitamin D status and body mass index (BMI) percentile of participants with high GS. Yet, no correlations were seen between vitamin D status and BMI percentile for participants with a low-to-moderate genetic score (GS) (GS ≤ 2). These results suggest that IGF1 genetic scores associated with elevated circulating IGF1 may indicate a tendency toward developing hypovitaminosis D-associated obesity.